Actinobacteria Microbiology to Synthetic Biology - Karthik, Loganathan (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book summarizes the basics of actinobacteria, from microbiology to synthetic biology. It focuses on diversity, NRPS, sesquiterpenes, lantipeptide, bioinformatics apparatuses, cloning, CRISPR, reverse engineering, FDA supported medications, and marine actinobacteria. It also covers the latest trends in drug discovery from actinobacteria, and introduces several recently developed bioinformatics and synthetic biology tools to explore new antibiotics from actinobacteria. Many natural products such as polyketides, isoprenoids, phenazines, peptides, indolocarbarbazoles, sterols, and others have been isolated and characterized from actinobacteria. Some products are synthesized by the non-ribosomal peptide synthetases (NRPSs), polyketide synthases (PKSs), or other functional genes. Although genome sequencing has uncovered the differing qualities of these chemicals, recognizing new items and their biosynthetic pathways is still under examination. Cryptic metabolic pathways have been explored using molecular techniques or culture-dependent approaches. In recent years, researchers' primary interest is to identify the specific conditions or agents that wake the cryptic antibiotics. Several bioinformatics and synthetic biology tools were developed to explore new antibiotics from actinobacteria. The book comprises 14 chapters with different aspects of application and utilization of actinomycetes from the microbiology; systems biology, pharmacology of natural products, bioinformatics, actinomycete and its diversity, CRISPR, artificial Intelligence, synthetic biology, metabolic engineering, expressional studies, and biosynthetic gene clusters. The book delivers useful information on actinomyces to researchers, novices in genome designing, specialists, clinicians, policymakers, and professionals.
Chapter 1. Actinomycetes: Microbiology to Systems Biology -- Chapter 2. Diversity of actinobacteria in various habitats -- Chapter 3. Traditional Screening and Genome Guided Screening of Natural Products from Actinobacteria -- Chapter 4. The relationship between actinobacteria and rice -- Chapter 5.Non-ribosomally and ribosomally synthesized bioactive peptides - NRPS and RiPPs from actinobacteria -- Chapter 6. Genome Data Mining, Chemistry and Bioactivity of Sesquiterpenes from Actinobacteria -- Chapter 7. Genome Data Mining, Chemistry and Bioactivity of Sesquiterpenes from Actinobacteria -- Chapter 8. Cloning and Heterologous expression of Natural products from Actinobacteria -- Chapter 9. Synthetic Biology and Metabolic Engineering in Actinobacteria for Natural Product Production -- Chapter 10. CRISPR ERA: CURRENT APPLICATIONS AND FUTURE PERSPECTIVES ON ACTINOBACTERIA -- Chapter 11. Uncultured Actinobacteria and Reverse engineering and Artificial Intelligence role in future -- Chapter 12. Cultivation and Diversity of Marine Actinomycetes: Molecular Approaches and Bioinformatics Tools -- Chapter 13. Antimicrobial Potential and Metabolite Profiling of Marine Actinobacteria -- Chapter 14. Pharmacology of FDA Approved Medicines from Actinobacteria.
Keywords: Synthetic Biology; Bioinformatics; Drug delivery systems; Industrial microbiology; Synthetic Biology; Bioinformatics; Drug Delivery; Industrial Microbiology